Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T14:55:19+01:00
G)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)3(y+6)-y=2(y+9)
3y+18-y = 2y+18
3y-y-2y=18-18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-10 = 3
x-6x = 3+7+10
-5x = 20 / : (-5)
x = -4
2010-02-28T14:55:59+01:00
G)
-(4+x)=2(3-x)
-4+x=6-3x
x+3x=6+4
4x=10/4
x=5/2
x=2,5

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
2y-2y=18-18
0=0

i)
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3
15x=20/15
x=20/15
x=4/3
2010-02-28T14:57:38+01:00
G)
-4-x=6-2x
x=10
x=5

h)
3y+18-y=2y+18
-2y+18=-2y+18
0=0
y nalezy do R

i)
x-7-6x-10=3
-5x=20
x=-4